Implementation of POE Learning Model to Improve Students' Critical Thinking Abilities on the Material of Ion Equilibrium and pH of Buffer Solutions - Nurfazela, Nurfazela; Copriady, Jimmi; Albeta, Sri Wilda (Pendidikan Kimia FKIP Universitas Jambi, 2025)
This study was motivated by the low level of students' critical thinking skills, which is evident from their difficulties in solving complex problems. Students tend to rely on memorized formulas rather than analyzing the problems beforehand. The objective of this study was to investigate the improvement of students’ critical thinking skills on the topic of ionic equilibrium and buffer solution pH in Grade XI at SMAN 2 Tambang, through the implementation of the Predict-Observe-Explain (POE) learning model. The research was conducted in the even semester of the 2024/2025 academic year using a randomized control group pretest-posttest design, involving two classes: class XI-1 as the experimental group and class XI-4 as the control group. Data collection was carried out using pretest scores as baseline data for normality and homogeneity tests, and the difference between pretest and posttest scores was used for hypothesis testing. Data analysis techniques included normality tests, homogeneity tests, and hypothesis testing. The results indicated that students’ critical thinking skills improved significantly after the application of the POE model. This improvement was confirmed by the hypothesis test, where the significance value was 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Therefore, the implementation of the POE learning model is recommended as an effective alternative to enhance students’ critical thinking skills, particularly in learning materials related to ionic equilibrium and buffer solution pH. Keyword: Critical thinking skills, Ionic equilibrium, buffer solution, POE model.